Choroidal Thickness in Nonarteritic Anterior Ischaemic Optic Neuropathy: A Study with Optical Coherence Tomography - Dias-Santos, A (2017)
Nonarteritic anterior ischemic optic neuropathy (NA-AION) is the most common nonglaucomatous optic neuropathy in adults over 50 years of age. It is usually related to cardiovascular risk factors. The primary objective of this study was to evaluate choroidal thickness in patients with chronic NA-AION, and the secondary objective was to evaluate macular thickness in these patients. This cross-sectional study compared two groups: group 1 included 20 eyes of 20 patients with chronic NA-AION, and group 2 included 31 eyes of 31 healthy controls. In both groups, the choroidal thickness was measured using the enhanced depth imaging program of Heidelberg Spectralis® optical coherence tomography (Heidelberg Engineering, Heidelberg, Germany). The macular thickness was also measured using the automatic software of the same device. The mean follow-up time after NA-AION in group 1 was 57.17 ± 26.92 months. The mean choroidal thickness of the posterior pole was 244.38 ± 61.03 µm in group 1 and 214.18 ± 65.97 µm in group 2 (p = 0.004). The mean macular thickness was higher in group 2. Macular thickness is reduced in eyes that had an episode of NA-AION, whereas choroidal thickness is generally higher in these eyes when compared with normal eyes. The increase in choroidal thickness may be due to a local dysfunction in vascular autoregulatory mechanisms, which may predispose to ischemic phenomena.